2006
DOI: 10.1242/jcs.02952
|View full text |Cite
|
Sign up to set email alerts
|

Severe muscular dystrophy in mice that lack dystrophin and α7 integrin

Abstract: The dystrophin glycoprotein complex links laminin in the extracellular matrix to the cell cytoskeleton. Loss of dystrophin causes Duchenne muscular dystrophy, the most common human X-chromosome-linked genetic disease. The α7β1 integrin is a second transmembrane laminin receptor expressed in skeletal muscle. Mutations in the α7 integrin gene cause congenital myopathy in humans and mice. The α7β1 integrin is increased in the skeletal muscle of Duchenne muscular dystrophy patients and mdx mice. This observation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
143
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(147 citation statements)
references
References 66 publications
3
143
0
1
Order By: Relevance
“…Several lines of evidence suggest positive feedback in the regulation of laminin and ␣ 7 -integrin expression (6,13,15). To test the hypothesis that laminin regulates ␣ 7 -integrin expression, ␣ 7 ␤gal ϩ/Ϫ myoblasts were exposed to 0-200 nM laminin-111 for 24 h. The activity of the ␣ 7 -integrin promoter was measured by ␤-galactosidase cleavage of the nonfluorescent compound fluorescein di-␤-D-galactopyranoside (FDG) to fluorescein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence suggest positive feedback in the regulation of laminin and ␣ 7 -integrin expression (6,13,15). To test the hypothesis that laminin regulates ␣ 7 -integrin expression, ␣ 7 ␤gal ϩ/Ϫ myoblasts were exposed to 0-200 nM laminin-111 for 24 h. The activity of the ␣ 7 -integrin promoter was measured by ␤-galactosidase cleavage of the nonfluorescent compound fluorescein di-␤-D-galactopyranoside (FDG) to fluorescein.…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic overexpression of the ␣ 7 -integrin in the skeletal muscle of severely dystrophic mice improves muscle pathology and increases lifespan (11). Conversely, loss of the ␣ 7 -integrin in mdx mice results in a more severe dystrophic phenotype and reduced viability, with mice dying prematurely by 4 weeks of age (12,13). Together, these results support the hypothesis that the ␣ 7 ␤ 1 -integrin is a major modifier of muscle disease progression, and drug-based therapies that boost its expression could alleviate DMD.…”
mentioning
confidence: 99%
“…In the integrin a7-deficient mice, the myotendinous junction, the primary site of force transmission between the muscle and the tendon, was severely disrupted, indicating an important role of integrin a7 in the organization and/or maintenance of the myotendinous junction (Mayer et al 1997;Nawrotzki et al 2003). The generation of integrin a7/dystrophin-or integrin a7/ sarcoglycan-double mutant mice demonstrates an essential role for integrin a7 in the maintenance of the DGC-deficient muscle plasma membrane (Allikian et al 2004;Guo et al 2006;Rooney et al 2006). Overexpression of integrin a7 in dystrophin/utrophin double mutant mice, a mouse model for DMD, ameliorates the muscle disease phenotype (Burkin et al 2001).…”
Section: Extracellular Matrix Proteins and Receptorsmentioning
confidence: 98%
“…4A). Recent studies [27][28][29] indicate that the DGC and the laminin-binding α7β1 integrin perform overlapping functions in skeletal muscle. However, western blot analysis demonstrated that γ cyto -actin was not altered in dystrophic α7 integrin null muscle compared to control (Fig.…”
Section: Resultsmentioning
confidence: 99%